2011
DOI: 10.1007/s10551-011-0878-x
|View full text |Cite
|
Sign up to set email alerts
|

Study of Commitment Antecedents: The Dynamic Point of View

Abstract: perception of organizational politics, perception of equity, trust, organizational commitment,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 61 publications
1
18
2
1
Order By: Relevance
“…The study finds that the impersonal trust positively affects organizational commitment. This study supports the researches by Utami et al (2014), Baek and Jung (2014), Kliuchnikov (2011), Chen and Indartono (2011), Zeffane et al (2011) and Bouckenooghe (2012), that organizational trust has a positive effect on organizational commitment.…”
Section: The Influence Of Impersonal Trusts On Organizational Commitmentsupporting
confidence: 91%
See 2 more Smart Citations
“…The study finds that the impersonal trust positively affects organizational commitment. This study supports the researches by Utami et al (2014), Baek and Jung (2014), Kliuchnikov (2011), Chen and Indartono (2011), Zeffane et al (2011) and Bouckenooghe (2012), that organizational trust has a positive effect on organizational commitment.…”
Section: The Influence Of Impersonal Trusts On Organizational Commitmentsupporting
confidence: 91%
“…This study supports the research of Jam et al (2011), who perceived that organizational politics has no effect on organizational commitment. However, this study differs from that of Vigoda (2000), Chen and Indartono (2011), Utami et al (2014), Butt et al (2013), Rong and Cao (2015), who perceived organizational politics as negatively affecting organizational commitment.…”
Section: The Influence Of Perceived Organizational Politics On Organicontrasting
confidence: 75%
See 1 more Smart Citation
“…Studies have shown that employees with a strong sense of trust in their organizations tend to have a strong sense of job satisfaction (Fard and Karimi, 2015), and their creativity (Jiang and Chen, 2017), performance (Çelik et al 2011) and organizational commitment (Mete and Serin, 2014) are at a high level, while their burnout (Çelik et al, 2011), organizational silences (Fard and Karimi, 2015), and cynicism (Durmaz et al, 2012) are at a low level. Studies investigating the relationship between PBP and trust have shown that if an individual's perception of political behavior toward their colleagues and managers in the organization decreases, their trust in them will increase (Parker et al, 1995;Robbins and Judge, 2013;Chen and Indartono, 2011). The relationship between perception of political behavior and organizational trust can be addressed from the perspective of social change theory (Blau, 1964).…”
Section: The Relationship Between Pbp and Organizational Trustmentioning
confidence: 99%
“…These authors suggest that employees may have access to healthy organizational practices provided by the organization and, nonetheless, perceive that the organization is not supportive enough toward the team. However, many other variables have been suggested as playing a role in this process such as the perceptions of organizational equity and/or organizational politics (Chen &Indartono, 2011), organizational trust (Acosta, Salanova, &Llorens, 2012), and organizational justice . Even more, organizational affective commitment was not a mediator in the association between healthy organizational practices and team performance.…”
Section: Theoretical Implicationsmentioning
confidence: 99%